The Contribution of Social Identity to Conformity in Korean Pop Fans - K. Y.S. Putri; Luthfi Fazli (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2024)
Riots in a certain group have become widespread today, and the activities of many irresponsible people acting on behalf of various groups have resulted in an unfavorable perception of that group among the general public. This is true for K-Pop fans, who regularly experience negative stigma as a result of irresponsible behavior. As a result, many K-Pop fans attempt to define themselves and their groups as social groups that are not like what the majority of people imagine, both stigmatizing and seeing them in a negative way. The goal of this research is to explore how social identity influences compliance among K-Pop enthusiasts. This study employed a quantitative research strategy, collecting data through questionnaires with two measuring instruments: the social identification scale and the conformity scale. The population under investigation includes individuals and social groupings, with a particular focus on K-Pop fans residing in DKI Jakarta. The samples used in this study comprised both individual K-Pop fans and non-fans; there were 82 respondents in total: 40 non-fans and 42 K-Pop aficionados. The research being conducted seeks to discover whether, as direct K-Pop enthusiasts believe, social identity plays a role in conforming to the fandom, as well as the perspectives and thoughts of non-K-Pop fans. A simple regression analysis was used for this study's data analysis. The results of the study show that social identity influences compliance by 56.3%.